Engineering analysis of the high-density heterotrophic cultivation of mung bean sprouts. Issue 8 (2nd August 2016) - Tamate, Haruka; Nakai, Ran; Nakamori, Yasuyuki; Esashi, Masahiro; Iwamoto, Yasushi; Tsukada, Yoshihiro; Saito, Mika; Ishikawa, Daitaro; Fujii, Tomoyuki
Abstract: This study investigated the heterotrophic growth behavior of mung beans cultivated in an individual bed under water supply. The fresh weight of mung beans in the bed was estimated, and changes in temperature, and oxygen and carbon dioxide concentrations were recorded during the cultivation period. The specific growth rate, oxygen uptake rate, and carbon dioxide evolution rate, based on the fresh weight in the bed, were calculated. Growth under heterotrophic cultivation can be classified into the following three stages. Reductions in specific oxygen uptake rate, specific carbon dioxide evolution rate, and specific energy production rate corresponded to that of specific growth rate. Indicators of biological activity related to oxygen and carbon dioxide were evaluated quantitatively for beds under high-density heterotrophic cultivation. Moreover, the results obtained from this study successfully demonstrate that there is a relationship between the growth of mung beans and indicators of biological activity. Graphic abstract: : Growth behavior of mung bean sprouts was quantitatively investigated for the high-density heterotrophic cultivation in an individual bed under dark condition.